Prevalence of dengue antibodies in healthy children and adults in different Colombian endemic areas. (February 2020) - Velandia-Romero, Myriam L.; Coronel-Ruiz, Carolina; Castro-Bonilla, Lorena; Camacho-Ortega, Sigrid; Calderón-Peláez, María Angélica; Castellanos, Angélica; Olano, Víctor Alberto; Porras, Alexandra; Arevalo-Herrera, Myriam; Villamil-Gómez, Wilmer; Castellanos, Jaime E.
Graphical abstract: Highlights: Dengue seroprevalence is over 90% in Colombian volunteers from 4 to 95 years old. The high percentages of IgM (15%) or PCR (8.4%) positive samples show a wide and persistent DENV circulation and a large number of asymptomatic infections in the population. The high risk of DENV infection occurs equally in urban and rural areas of Colombia. Abstract: Objectives: Colombia is a dengue hyperendemic country; however, the prevalence of antibodies against dengue in the general population including the inhabitants of rural areas is unknown. This study aimed to determine the prevalence of dengue IgM and IgG antibodies in healthy children and adults in urban and rural areas of seven different endemic regions in Colombia between 2013 and 2015. Design or method: Blood samples from healthy volunteers (1, 318) were processed by serology (by indirect IgG and capture IgM and IgG ELISA) and molecular tests to detect viral RNA and circulating serotypes. Results: The seroprevalence of IgG for dengue were 85% in children and over 90% for adults. In addition to the high IgM positive rate (14.9%) and secondary recent infection marker rate (capture IgG, 16%), 8.4% of the healthy volunteers were positive for dengue virus (DENV) RNA. Conclusion: This study confirmed the broad and permanent circulation of DENV in Colombia and the high rates of infection and reinfection suffered by its inhabitants. This information can be used by the health authorities to strengthen vector control and vaccine policies and review the algorithms of diagnosis and disease management in children and adults.